2009
DOI: 10.1159/000232971
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Integrin-Linked Kinase with a Small Interfering RNA Inhibits Endothelial Cell Migration, Proliferation and Tube Formation in vitro

Abstract: Purpose: To investigate the role of integrin-linked kinase (ILK) in endothelial cell migration, proliferation and tube formation in vitro. Materials and Methods: Cultured RF/6A cells were knocked down for ILK using small interfering RNA (siRNA). Cellular ILK expression was quantified by real-time quantitative PCR and Western blot analysis. Cell migration was measured by cell counting in modified Boyden chambers, while microfilament dynamics were assessed by immunofluorescence analysis. Cell cycling was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…The migration was suppressed by disrupting the F-actin assembly. 36 Our study confirmed that the ILK/AKT pathway was possibly involved in wound contraction by regulating wound fibroblast migration. ILK-mediated regulation of migration may be related to fibronectin.…”
Section: Ilk-pi3k/akt Pathway and Wound Contraction G LI Et Alsupporting
confidence: 76%
“…The migration was suppressed by disrupting the F-actin assembly. 36 Our study confirmed that the ILK/AKT pathway was possibly involved in wound contraction by regulating wound fibroblast migration. ILK-mediated regulation of migration may be related to fibronectin.…”
Section: Ilk-pi3k/akt Pathway and Wound Contraction G LI Et Alsupporting
confidence: 76%
“…21,34,35 ILK also has a critical role in cardiac development and function, particularly as a component of the cardiac stretch sensor. 36 However, little is known about the postnatal physiological role of ILK in relation to NO synthesis and vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that VEGF is the most critical growth factor for angiogenesis, and it plays a key role in EC biology. Guo et al (2009) observed that silencing ILK with siRNA significantly reduced VEGF secretion in the culture medium of RF/6A cells. So, the observed phenotype in pDNA-ILK EPCs prompted us to investigate the expression of VEGF using western blot and ELISA.…”
mentioning
confidence: 92%